The Dark Side of Desire: A Psychoanalytic Analysis of Trauma in Talk to Me (2022) - Melly Melly; Irma Rahmawati (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
Trauma is a psychological response rooted in the subconscious and shaped by past experiences, often intensified by social influences. This study explores how Talk to Me (2022) portrays trauma through the lens of Jacques Lacan’s psychoanalytic theory, focusing on the concepts of the Real, desire, and object a. The film presents possession as a metaphor for psychological fragmentation, with the protagonist Mia’s unresolved grief leading to obsession, identity collapse, and emotional deterioration. The embalmed hand symbolizes object a, an unattainable object of desire, while Mia’s pursuit of connection with her deceased mother triggers a confrontation with the Real, exposing the raw terror of psychic disintegration. Using qualitative methods, this study analyzes the film’s narrative and symbolism through observation, film analysis, and supporting academic sources. Findings reveal that Talk to Me reimagines possession as a reenactment of trauma, where each encounter intensifies inner voids. Ultimately, the film suggests that closure from trauma may not emerge through reunion, but through self-sacrifice and painful acceptance.